Aptamer mediated niosomal drug delivery. Issue 91 (14th September 2016) - Seleci, Didem Ag; Seleci, Muharrem; Jochums, André; Walter, Johanna-Gabriela; Stahl, Frank; Scheper, Thomas
Abstract : Development of nanoscale carrier systems for targeted drug delivery is crucial for cancer treatment. Abstract : Development of nanoscale carrier systems for targeted drug delivery is crucial for cancer treatment. The current methods of drug delivery exhibit some problems such as lack of therapy efficiency at the desired parts of the body, degradation of the drug before reaching the desired tissue and limitations in cellular penetration. In this work, a novel drug delivery platform was developed to overcome these problems and to enable specific and efficient uptake into the cells. The surface of the synthesized polyethylene glycolated niosomes (PEGNIO) was modified with cell penetrating peptide (CPP) and cell specific MUC1 (S2.2) aptamer, and doxorubicin (DOX) as a cancer model drug was encapsulated in this platform. Fluorescence microscopy and flow cytometry analysis were used to investigate the cellular uptake and intracellular distribution of the DOX loaded niosomal formulation. In vitro cytotoxicity studies were carried out using MUC1 positive HeLa and negative U87 cells. Moreover, dynamic light scattering (DLS), zeta potential measurements and fluorescence absorption spectroscopy were performed to determine the vesicle size, as well as charge and spectroscopic properties of the conjugates. From these results, this novel aptamer mediated niosomal drug delivery platform may have application potential in targeted drug delivery towards MUC1-overexpressing tumors.